Penerapan Hukum Tilang Elektronik Dikota Medan Perspektif Fiqh Siyasah - Z, M Yakub; Firmansyah, Heri (LPPM Universitas Ekasakti Padang, 2023)
The use of Tilang Elektronik is expected to be effective in achieving the goal of prosecuting traffic violations, even though there is an obstacle, namely that people in Indonesia do not understand the technical aspects. Based on the problems discussed in this journal, the formulation of the problems that will be raised from this research include: 1.) How is the Law Implemented Regarding Electronic Ticketing in Medan City? 2.) How is Fiqh Siayasah's review of electronic e-tickets? Meanwhile the research method used is an empirical research method which is influenced by the doctrine of legal sociology (sociology of law) and sociological legal science (sociological jurisprudence). Empirical research is carried out on research on facts that occur in the field, therefore researchers carry out data collection techniques. In order for the implementation of the electronic ticketing law to work, it is necessary to regulate the law with regulations issued by authorized officials, so that these regulations have a legal dimension that guarantees certainty that the law functions as a regulation that must be obeyed. Based on the description above regarding Siyasah syar'iyah, Electronic Ticketing is included in one of the laws and regulations that can guide humanity to benefit. In this case, these regulations were created to regulate and manage human life in protecting the safety of motorbike users who are used for the benefit of people who use transportation.